The trolls of Wall Street : how the outcasts and insurgents are hacking the markets - Popper, Nathaniel (Dey St., an imprint of William Morrow, 2024)
This dramatic story shows how two self-proclaimed "degenerates" made WallStreetBets, a subreddit focused only on risky financial trading, a cultural movement by harnessing the power of memes and trolling to create a new kind of online community, changing how an entire generation thinks about money, investing and themselves.